Nutraceutical Investigations of Commelina diffusa Burm. F. Leaves- A Popular Wild Vegetable - Kamble, Sajnay (Plantae Scientia, 2019)
Aqueous leaf extracts of Commelina diffusa was evaluated for food value. The results show that the proximate and vitamin compositions of Commelina. Diffusa included mainly moisture (83.36%), carbohydrate (6.32%), vitamin C (44.80 mg/100g dry weight), vitamin B3 (63.18mg/100g) and vitamin B2 (8.30 mg/100g) respectively. The mineral contents of the defatted leaf extracts were found to be Na (69.32mg/100g), Ca (232.00mg/100g) and Mg (84.28mg/100g). The proximate, vitamin and mineral compositions obtained suggest that the leaves, as cheap sources of vitamins C, B3 and B2, as well as other macro-and micronutrients, can be incorporated into human and animal diet to meet their recommended daily allowances. The content of flavonoids and vitamin C in the leaf extracts also suggests possible anti-oxidant effects of these leafy vegetables.